Implementation of the Electronic Information and Transaction Law on the Culture of Online Buying and Selling Transactions in Protecting Consumers - Muhammad Restu Arrasyiid; Stanley Muljadi Art; Muhammad Rangga Arya Putra (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
Technological developments bring changes to human life, especially social and cultural aspects. Technological developments lead to discoveries. One of them is the ease of buying products that were originally done conventionally to become digital. However, technological developments have given rise to cybercrime, namely in the form of fraud in buying and selling transactions through electronic media. The method used is qualitative research, which aims to describe and analyze changes in behavior in the community related to buying and selling activities that were originally done conventionally to become digital. In online buying and selling transactions, its application requires protection in the UUPK and the ITE Law but in the ITE Law article 28 paragraph (1) when implemented the article makes various assumptions about who the legal subject found in the interpretation of differences of opinion which states that the subject must be a producer while the elements clearly state each person, this confuses the standard as to what constitutes a person as a consumer. In the application of the ITE Law, it is felt that it is still not absolute in fulfilling legal certainty because it does not have a broad meaning about who a consumer is so the phrase should be given a detailed explanation to create legal certainty against potential violations in online buying and selling transactions, of course, with the hope that this regulation can successfully answer public concerns. will guarantee and feel safe when shopping online.